2021
DOI: 10.1109/access.2021.3081818
|View full text |Cite
|
Sign up to set email alerts
|

A Full Featured Configurable Accelerator for Object Detection With YOLO

Abstract: Object detection and classification is an essential task of computer vision. A very efficient algorithm for detection and classification is YOLO (You Look Only Once). We consider hardware architectures to run YOLO in real-time on embedded platforms. Designing a new dedicated accelerator for each new version of YOLO is not feasible given the fast delivery of new versions. This work's primary goal is to design a configurable and scalable core for creating specific object detection and classification systems base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In addition, by the up-sampling of the detection head of YOLOv5 in the addition of a detection head based on the Path Aggregation Network, the challenge of dense object distribution was mitigated. Authors [40] in their work demonstrated that the YOLOV5 architecture is not only a fast object detector but also achieved accuracy that is plausible to that of Faster R-CNN. In a similar study, authors [41] proved that the YOLO model can adequately classify and detect multiple objects in real-time, which makes it suitable as an underlying detector for the anti-drone system.…”
Section: Related Work On Drone Detection Techniques and Technologiesmentioning
confidence: 84%
“…In addition, by the up-sampling of the detection head of YOLOv5 in the addition of a detection head based on the Path Aggregation Network, the challenge of dense object distribution was mitigated. Authors [40] in their work demonstrated that the YOLOV5 architecture is not only a fast object detector but also achieved accuracy that is plausible to that of Faster R-CNN. In a similar study, authors [41] proved that the YOLO model can adequately classify and detect multiple objects in real-time, which makes it suitable as an underlying detector for the anti-drone system.…”
Section: Related Work On Drone Detection Techniques and Technologiesmentioning
confidence: 84%
“…Compared to [40], the proposed work was slower and less efficient in terms of BRAMs but more efficient in terms of LUT and similarly efficient in terms DSP. The lower BRAM efficiency has to do with the fact that BRAM contents (weights and activations) are shared by multiple cores.…”
Section: Comparison With Other Fpga Implementationsmentioning
confidence: 97%
“…The solution does not apply to real-time applications but provides a YOLO solution in a low-cost FPGA. Recently, another implementation of Tiny-YOLOv3 [40] with a 16-bit fixed-point format achieved 32 FPS in a UltraScale XCKU040 FPGA. The accelerator runs the CNN and pre-and post-processing tasks with the same architecture.…”
Section: Convolutional Neural Network Accelerators In Fpgamentioning
confidence: 99%
See 1 more Smart Citation
“…Also, FPGA can quickly update the design with its programmability and can be deployed quickly. Therefore, there are several researches on DCNN accelerator based on FPGA [9,10].…”
Section: Introductionmentioning
confidence: 99%